The Role of Dietary Fiber and Probiotics in Improving Lipid Profile in Obesity: A Literature Review - Annisa Nabilla; Helmizar Helmizar; Susmiati Susmiati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Obesity is a major public health problem that is closely associated with dyslipidemia and an increased risk of metabolic and cardiovascular diseases. Dietary fiber and probiotics have been widely explored as non-pharmacological dietary approaches to improve lipid profiles in obesity; however, evidence from experimental and clinical studies remains fragmented and requires systematic synthesis. This literature review aimed to synthesise current evidence on the role of dietary fiber and probiotics in improving lipid profiles under obese or metabolically compromised conditions. A literature search was conducted using Google Scholar, PubMed, and ScienceDirect to identify relevant studies published between 2020 and 2025. Studies assessing the effects of dietary fiber or probiotic interventions on lipid profile parameters in animal models or human subjects with obesity or metabolic disorders were included. The initial search resulted in 274 articles, which were subsequently screened for eligibility based on predefined inclusion and exclusion criteria. After screening, Six eligible studies met the inclusion criteria and were analysed qualitatively. The included studies consistently demonstrated that dietary fiber and probiotic interventions were associated with improvements in lipid profiles, including reductions in total cholesterol, triglycerides, and low-density lipoprotein cholesterol, alongside increases in high-density lipoprotein cholesterol. Several studies also reported concurrent reductions in body weight, visceral fat accumulation, or glycaemic parameters, indicating broader metabolic benefits. Dietary fiber and probiotics show potential as complementary, non-pharmacological strategies for improving lipid profiles in obesity. These findings support the development of functional food formulations incorporating fiber- and probiotic-based components.